Does Energy Consumption Volatility Affect Real GDP Volatility? An Empirical Analysis for the UK - Rashid, Abdul; Kandemir Kocaaslan, Ozge (International Journal of Energy Economics and Policy, 2013)
This paper empirically examines the relation between energy consumption volatility and unpredictable variations in real gross domestic product (GDP) in the UK. Estimating the Markov switching ARCH model we find a significant regime switching in the behavior of both energy consumption and GDP volatility. The results from the Markov regime-switching model show that the variability of energy consumption has a significant role to play in determining the behavior of GDP volatilities. Moreover, the results suggest that the impacts of unpredictable variations in energy consumption on GDP volatility are asymmetric, depending on the intensity of volatility. In particular, we find that while there is no significant contemporaneous relationship between energy consumption volatility and GDP volatility in the first (low-volatility) regime, GDP volatility is significantly positively related to the volatility of energy utilization in the second (high-volatility) regime. Keywords: energy consumption volatility; GDP volatility; asymmetry; Markov switching ARCH models; Markov regime switching models JEL Classifications: C22; E32